Hydroponic mint cultivation using biofertilizer as nutritive solution (Research, Society and Development, 2020)
Main component of the hydroponic system, the nutritive solution attends the mineral requirements of plants in their growing. However, the constant high use of commercial fertilizers can become expensive for the grower. Thus, the objective was to investigate the viability of using partial or total biofertilizer in nutritive solution in mint cultivation. The experiment was conducted in a greenhouse for 60 days in a completely randomized design with three treatments: 100% Biofertilizer; 50% Biofertilizer + 50% of the mineral nutrient solution; 25% Biofertilizer + 75% of the mineral nutrient solution and the 100 %mineral nutrient solution as positive control, in a structure with 56 plots according to the Nutrient Film Technique. The length of the plants that did not show significant differences between the treatments was evaluated. The values of fresh matter, dry matter and leaf area in partial substitution (50 or 25% of biofertilizer) showed an increase in relation to the mineral nutritive solution, demonstrating its viability. Thus, this increase in productivity can generate savings in the use of mineral fertilizers.